Mechanical and moisture diffusion behaviour of hybrid Kevlar/Cocos nucifera sheath reinforced epoxy composites - Arockiam, Naveen Jesu; Jawaid, Mohammad; Zainudin, Edi Syams; Hameed Sultan, Mohamed Thariq; R., Yahaya (Elsevier, 2019)
The aim of this research is partial replacement of plain woven Kevlar 29(K) with naturally woven cocous nucifera sheath (CS) waste. Laminated K/CS reinforced epoxy hybrid composites were fabricated by hand lay-up method followed by hot compression moulding with 105 °C temperature at 275 bar pressure for 1 h. The total fibre loading of the hybrid composite was maintained 45 wt.% and the ratio of Kevlar and Cocous nucifera sheath varies in weight fraction of 100/0, 75/25, 50/50, 25/75, and 0/100. Mechanical (tensile, flexural, impact), moisture diffusion and morphological behaviour of the laminated composites were evaluated. The results showed that the hybrid composites (75/25) declined the tensile strength by 19% compared to Kevlar fabric reinforced epoxy composites. But, the hybrid composites (75/25) exhibited highest flexural strength (175 MPa) and flexural modulus (18 GPa) than pure Kevlar reinforced epoxy composites. Moreover, the impact toughness of hybrid composites (86 kJ/m2) at 75/25 wt.% showed good agreement with the pure Kevlar fabric reinforced polymer composites (90 kJ/m2). From the moisture diffusion analysis, hybrid composites (75/25) exhibited better moisture resistance. Statistical analysis of the results has been carried out using one way-ANOVA (analysis of variance) and it shows that there is a statically significant difference between the obtained mechanical properties of the laminated composites. Morphology of the tensile fractured laminates showed the delamination's, matrix cracking and fibre/matrix adhesion. From the results, it has been concluded that naturally woven Cocos nucifera sheath has the potential to replace Kevlar fabric in the polymer composites exclusively for defence applications.